Variation of fatty acid composition in seed oil in the collection of induced oil flax (Linum humile Mill.) mutants - A. V. Tigova; A. I. Soroka (Вавиловский журнал генетики и селекции, 2018)
A wide variety of application fields for flax seeds requires for breeders to develop new varieties with different characteristics, corresponding to the intended final product. The method of experimental mutagenesis is one of the ways to solve this problem. This method allows mutant lines with an array of morphometric and biochemical traits to be created from a single species and within a relatively short period of time. The article demonstrates that treatment of Linum humile Mill. seeds of the cultivars Iceberg and Solnech-ny with the new chemical mutagens DG-2, DG-6, DG-7, DG-9 (derivatives of dimethyl sulfate (DMS)) as well as with the mutagens DMS and EMS resulted in the production of mutant lines and accessions with altered morphometric and biochemical parameters. Seeds of the initial cultivars were treated with 0.5 and 0.05 % aqueous solutions of the above mentioned substances and planted in the field to raise M1, M2, and M3 generations. Ultimately, 27 types of mutations were identified and subdivided into five groups by morphometric characteristics. The fatty acid composition of seed oil for the isolated mutant specimens was studied: the content of palmitic, stearic, oleic, linoleic (w6) and lino-lenic (w3) acids, as well as the w6/w3 ratio. The statistical analysis showed significant distinctions between the mutant lines in the biochemical composition of the oil. A strong negative correlation between the content of linoleic and linolenic acids was demonstrated, as well as a positive relationship of average strength between the content of stearic and oleic acids for the both varieties. The mutant accessions obtained can be used as donor material for conducting breeding work on flax in various directions.